Subduction and accumulation of lawsonite eclogite and garnet blueschist in eastern Australia. (11th December 2019) - Tamblyn, Renée; Hand, Martin; Kelsey, David; Anczkiewicz, Robert; Och, David
Abstract: Lawsonite eclogite and garnet blueschist occur as metre‐scale blocks within serpentinite mélange in the southern New England Orogen (SNEO) in eastern Australia. These high‐ P fragments are the products of early Palaeozoic subduction of the palaeo‐Pacific plate beneath East Gondwana. Lu–Hf, Sm–Nd, and U–Pb geochronological data from Port Macquarie show that eclogite mineral assemblages formed between c. 500 and 470 Ma ago and became mixed together within a serpentinite‐filled subduction channel. Age data and P–T modelling indicate lawsonite eclogite formed at ~2.7 GPa and 590°C at c. 490 Ma, whereas peak garnet in blueschist formed at ~2.0 GPa and 550°C at c. 470 Ma. The post‐peak evolution of lawsonite eclogite was associated with the preservation of pristine lawsonite‐bearing assemblages and the formation of glaucophane. By contrast, the garnet blueschist was derived from a precursor garnet–omphacite assemblage. The geochronological data from these different aged high‐ P assemblages indicate the high‐ P rocks were formed during subduction on the margin of cratonic Australia during the Cambro‐Ordovician. The rocks however now reside in the Devonian–Carboniferous southern SNEO, which forms the youngest and most outboard of the eastern Gondwanan Australian orogenic belts. Geodynamic modelling suggests that over the time‐scales that subduction products accumulated, the high‐ P rocks migrated large distances ( ~ >1, 000 km) during slab retreat. Consequently, high‐ P rocks that are trapped in subduction channels may also migrate large distances prior to exhumation, potentially becoming incorporated into younger orogenic belts whose evolution is not directly related to the formation of the exhumed high‐ P rocks.